2015
DOI: 10.30664/ar.67573
|View full text |Cite
|
Sign up to set email alerts
|

Participation, metaphysics, and enlightenment: reflections on Ken Wilber’s recent work

Abstract: This article critically examines Ken Wilber’s (2006) recent work from a participatory perspective of human spirituality. After a brief introduction to the participatory approach, I limit my discussion to the following four key issues: a. the participatory critique of Wilber’s work, b. the cultural versus universal nature of Wilber’s Kosmic habits, c. the question of (post-)metaphysics in spiritual discourse, and d. the nature of enlightenment. The article concludes with some concrete directions in which to mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…By contrast, according to the cosmocentric view the role of transition function does not belong essentially to the self (i.e., ego or mental system) but belongs, instead, to the hierarchy of basic structures themselves (Washburn, 2003b). That is, development is assumed to emerge teleologically from the interaction of our immediate present experience with the structures or levels of transcendent consciousness (Ferrer, 2011; see also Ferrer, 2008). Combs and Krippner (2011) explained the evolution of consciousness as a "self-organizing, or autopoietic system, nested within a larger developmental autopoietic system" (p. 216).…”
Section: Secularized Self Cannot Account For Individuationmentioning
confidence: 99%
“…By contrast, according to the cosmocentric view the role of transition function does not belong essentially to the self (i.e., ego or mental system) but belongs, instead, to the hierarchy of basic structures themselves (Washburn, 2003b). That is, development is assumed to emerge teleologically from the interaction of our immediate present experience with the structures or levels of transcendent consciousness (Ferrer, 2011; see also Ferrer, 2008). Combs and Krippner (2011) explained the evolution of consciousness as a "self-organizing, or autopoietic system, nested within a larger developmental autopoietic system" (p. 216).…”
Section: Secularized Self Cannot Account For Individuationmentioning
confidence: 99%
“…Finally, Ferrer has suggested that spiritual systems should enable a movement beyond ecosocial injustice, leading to a more empathic and responsible attitude to the natural world, and a compassionate and altruistic attitude to social and global problems (Hartelius & Ferrer, 2013). Ferrer (2011a) also proposed that it is legitimate to speak of "shared spiritual power" in the sense of the "generative power of life, the cosmos and/or the spirit" (p. 127), while at the same time remaining free of ontological objectivity and without assuming the existence of any pregiven ultimate reality (Ferrer & Sherman, 2008a). …”
Section: International Journal Of Transpersonal Studies 19mentioning
confidence: 99%
“…Such processes, though less common than might be desired, are already present within transpersonal scholarship-beginning perhaps in the mid-1990s with critiques of Wilber's work (e.g., Ferrer, 1998, 2002, 2009Rothberg & Kelly, 1998;Wright, 1995Wright, , 1996. In concert with these have been calls for more careful approaches to philosophy (e.g., Ferrer, 2002), science (e.g., Friedman, 2002;MacDonald, 2013;Walach, 2013), and method (Berkhin & Hartelius, 2011;Friedman, 2013;Hartelius, 2007Hartelius, , 2014.…”
mentioning
confidence: 99%